Iodine status of pregnant women in iodine-sufficient regions: A tertiary care unit experience - Cigdem Tura Bahadir (Wolters Kluwer Medknow Publications, 2023)
Background: The recommended urinary iodine concentration (UIC) levels in the overall adult population is 100-199 μg/L whereas 150-249 μg/L in pregnant women. Objectives: The objective is to determine the prevalence and severity of iodine deficiency in pregnant women in Amasya, which is located in the Western Black Sea region in Turkey, where sufficient iodine levels were achieved in the normal population. Methods: In this single-center study, we retrospectively searched hospital patient records and identified pregnant women who were assessed for iodine levels between January 2019 and January 2021. A total of 408 pregnant women were found eligible for the study. Thyroid-stimulating hormone (TSH), free triiodothyronine, free thyroxine, antithyroid peroxidase antibodies, and antithyroglobulin antibodies in serum samples and UIC were evaluated and compared between the trimesters. Insufficient iodine intake in pregnancy was defined as UIC <150 μg/L. Results: Median UIC and median TSH levels were 129 (range 45-452) μg/L and 2.98 (range 0.01-71.2) μIU/ml, respectively. 81.1% of pregnant women had UIC <150 μg/L. Iodine intake was adequate in 17.4% of pregnant whereas excessive in 1.5%. Prevalence of iodine deficiency during 1st, 2nd, and 3rd trimesters were 82.1%, 82.4%, and 74.5%, respectively. There was no significant difference in UIC levels between trimesters (P = 0.399). 72.9% of pregnant womens had TSH >2.5 mIU/L in the 1st trimester. Conclusion: Iodine deficiency in pregnancy may exist in an iodine-sufficient population. Appropriate measures must be taken to ensure sufficient iodine levels in these individuals.